LITERATURE REVIEW : THE INFLUENCE OF PRODUCT DIFFERENTIATION, PRODUCT INNOVATION AND CUSTOMER EXPERIENCE ON CUSTOMER SATISFACTION ON SOMETHINC BEAUTY PRODUCTS IN NORTH BEKASI CITY - Kanizah (IJESM Indonesian Journal of Economics and Strategic Management, 2023)
This research is a literature review which aims toexamine the influence of product differentiation,product innovation and consumer experience onconsumer satisfaction with skincare products. Thisresearch tries to determine the influencing factors ofcustomer satisfaction with this product. This researchuses a quantitative approach with an unknownpopulation. However, with the hair, et al approach,this research used a minimum sample size of 75respondents. This research can be tested with SPSSstatistical tools by testing the feasibility of the dataand research hypotheses.